The economics of alcohol policy - Lehto, Juhani; World Health Organization. Regional Office for Europe (WHO regional publications, ISSN 0378-2255, 1995)
Conclusions (s. 48-50).
Keywords: alkoholikysymys; alkoholipolitiikka; alkoholivero; alkoholipolitiikka : taloudelliset vaikutukset